The Authority of Tabi'in Interpretation: Analysis of Qotadah bin Di'amah Al-Sadusi's Interpretation of the Verses of Fate - Islamie, Fikri; Ahmad, Khadher (Jurnal Iman dan Spiritualitas, 2025)
The interpretation of the Tabi'in is one of the interpretations that has a high position in interpretation. The narration taken from the Tabi'in is categorized by some scholars as the interpretation of bi al-ma'á¹¡Å«r, which in terms of narration, the interpretation of the Tabi'in has the same authority as the interpretation of the Companions. However, acceptance and rejection were expressed towards one of the Tabi'in scholars, Qotadah bin Di'amah, who was accused by some scholars of being a Qodariyyah scholar. This research was conducted using library research and aims to reveal the results of Imam Qotadah's interpretation, examining his position in the interpretation of the Tabi'in. The results obtained from this research are that through the analysis of his interpretation, no strong evidence was found that Qotadah was a Qodariyyah scholar, which further confirms his credibility which has implications for the authority of the Tabi'in interpretation.